PENGAWASAN PEMANFAATAN TATA RUANG DI KOTA BANDUNG - Dian Susanti (FISIP Universitas Langlangbuana, 2020)
The background of this research was the low effectiveness of the spatial utilization which done by Dinas Tata Ruang dan Cipta Karya on Bandung municipality. The conditions are assumed as an influence of under optimal controlling on spatial utilization. Based on the problems the quistionaire of this research is :”How the influence of controlling to the effectiveness of spatial utilization on Bandung Municipality”. To analyze the case in this research, the theory of controlling from Sujamto wich the dimention of controlling (1996:60) and the effectiveness theory from Yuchman and sheashore in Steers (1985:55-57) was being used. Based on the theories, the hypothesys was suggest:”The influence of controlling to the effectiveness of spatial utilization was caused by the implementing of direct controlling, indirerect controlling and the exeption as a dimention of controlling”. Method of survey explanatory was used in this research by data technique collecting samples throwing library and field study consist of observation, interview and questionare. The techniquest of collecting samples in this research where determined by probability sampling especially simple random sampling method and being analyzed with linier statistical regretion. The result of this research showed there were a positive influence of controlling to effectiveness of the space utilization, and besides such variables, there was other variables which influenced to the effectiveness of space utilization.